Old Testament difficulties being a collection of writings for working men - Ingram, A.F. Winnington (London, UK Society for Promoting Christian Knowledge, 1902)
Includes bibliographical references.
Old and frail. Donated by Mr R.C. Croucher
Keywords: Bible. O.T. -- introductions